Meta-analysis of Proton Pump Inhibitors in the Treatment of Pharyngeal Reflux Disease. (21st July 2022) - Jin, Xiulin; Zhou, Xufeng; Fan, Zongxian; Qin, Yingchun; Zhan, Junjie
Abstract : The present study aimed to examine the safety and healing effects of proton pump inhibitors (PPIs) in people with laryngopharyngeal reflux disease (LPRD). To find all relevant studies published before April 1, 2022, we searched the PubMed, Embase, Web of Science, Clinical Trials, Cochrane Library, CNKI, and Wanfang databases. For SLE, we looked for all randomized controlled clinical trials related to PPIs versus placebo-controlled treatment of LPRD. Overall efficiency, reflux symptom index (RSI), reflux finding score (RFS), improvement in cough and hoarseness, and adverse reactions were compared using the Review Manager 5.3. Using the reflux symptom index (RSI) as an outcome indicator for efficacy assessment, the PPI group showed significant improvement compared with the placebo group [MD = 3.35, 95% CI (1.34, 5.37, P < 0.05 )]. In terms of overall efficacy, the PPI group showed effectiveness, but its efficacy was not statistically significantly dissimilar from that of the placebo group [OR = 1.62, 95% CI (0.89, 2.95), P > 0.05 ].